MAXIMISING STUDENTS’ TASK SUBMISSION AND ENGLISH WRITING EXPRESSION THROUGH CANVAS LMS - Endah Yulia Rahayu (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2020)
Task submission often becomes the burdens of lecturers or teachers since they have to report it and use it their students’ assessment result. However, in today’s Covid-19 epidemic season, online Learning Management System (LMS), which has abundant multimedia resources and conduct online assessments can help teachers to collect and report their students’ task-submission. Besides that, LMS can make their students express their thought in English in various genres. This study highlights the use of LMS Canvas in teaching Entrepreneurship for the eighth-semester students of English Department of UNIPA Surabaya. Sixty-two students registered themselves after receiving notification e-mail from the Canvas in order to take part in one of their compulsory courses – Entrepreneurship. This study applies descriptive quantitative and convenient sampling. In the context of learning Entrepreneurship, withing a half-semester, the students learned five units, and 95% of them submit their written assignment in the LMS Canvas with the average score 75. Meanwhile, for their English writing in their Entrepreneurship course’ tasks, they manage to write their inspired person, family, future life, their future business, character and personality, and write dream book. Those who did not submit their works cannot be contacted, although their name is registered in the Entrepreneurship class. It is evident since canvas always send a notification e-mail to both lecturer and students any lessons, tasks, and announcements from the lecturer. The students always get any information from their lecturer and class amidst this pandemic season.